Analisis dan Perancangan Sistem Absensi Karyawan Berbasis Website di SMP Santo Leo - Bintang Dwinanto Prakoso; Agus Budiyantara (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze and design a website-based employee attendance system at SMP Santo Leo as a solution to the weaknesses of the manual attendance system which is prone to recording errors, data loss, and inefficiencies in recapitulation and attendance monitoring. The design method uses the Unified Modeling Language (UML) approach to systematically visualize system needs and workflows. The system developed has the main features in the form of recording attendance in and out of the house, applying for permits, and making automatic attendance reports. The system test is carried out using the User Acceptance Test (UAT) method based on five aspects: functionality, ease of use, suitability, system performance, and interface display. The test results show that the user satisfaction rate is in the range of 85% to 92%, which is categorized as